자율주행자동차 평가를 위한 도심도로 교통사고 데이터 분석 및 상황 시나리오 개발 연구 - 노종민 (The Graduate School, Ajou University, 2024)
향후 상용화될 자율주행자동차의 안전성 평가에 있어 다양한 악조건을 가진 도심도로 환경을 고려하는 것이 필요하다. 또한, 자율주행자동차의 기능 및 안전성을 체계적으로 평가하기 위한 시나리오 기반의 평가 방법론이 여러 연구를 통해 수행되고 있다._x000D_ 이에 본 연구는 경찰청 교통사고 데이터를 바탕으로 국내 도심도로 중 광로와 대로를 대상으로 자율주행자동차의 주행 안전성을 평가하기 위한 상황 시나리오를 개발하였다. 교통사고 데이터와 도로구간 링크를 기초 데이터로 QGIS 프로그램을 통해 공간연산을 수행하여 광로 및 대로 구간에서 발생한 교통사고 데이터를 추출하였다. 이후, 교통사고 데이터의 사고경위 항목에 TF-IDF 기법을 적용하여 사고 상황과 관련된 주요 단어들을 키워드로 선정하였으며, 사고경위 항목의 서술구조 및 선정한 키워드에 기반한 데이터 해석 방법론을 설계하였다. 따라서, 광로 및 대로의 가로구간과 신호교차로에서 발생한 차대차 교통사고 데이터를 대상으로 데이터 분석을 수행하여 교통사고 상황 유형과 유형별 교통사고 건수를 도출하였으며, 도출한 상황 유형을 내용으로 자율주행자동차의 주행 안전성을 평가하기 위한 상황 시나리오 22건을 개발하였다. 또한, 개발한 복수의 상황 시나리오를 군집화 및 유형화하기 위한 시나리오 Pool을 구축하였다._x000D_ 본 연구를 통해 비정형데이터인 교통사고 데이터로부터 공간연산 및 텍스트 마이닝을 통해 광로 및 대로 구간의 교통사고 유형을 도출하는 방법과 이에 기반한 상황 시나리오를 개발하는 과정과 결과를 제시하였다. 개발한 상황 시나리오는 도심도로의 광로 및 대로 구간을 배경으로 자율주행자동차의 주행 안전성을 평가하는 데 필요한 다양한 위험 상황들을 정의하며, 실제 발생한 교통사고 데이터를 시나리오의 도출 근거로 사용하여 현실성 높은 교통상황을 반영할 수 있었다.|It is necessary to consider urban road environments with various adverse conditions in evaluating the safety of autonomous vehicles to be commercialized in the future. In addition, scenario-based assessment methodologies for systematically evaluating the functions and safety of autonomous vehicles are being conducted through several studies._x000D_ This study developed functional scenarios to assess the driving safety of autonomous vehicles on urban roads in Korea, specifically focusing on boulevards and avenues based on traffic accident data from the National Police Agency. Traffic accident data that occurred on boulevards and avenues were extracted by performing spatial calculation through the QGIS program based on traffic accident data and road section links. After that, TF-IDF technique was applied to the accident circumstances field of the accident data to select keywords related to accident situations. And a methodology for interpreting data was designed based on the descriptive structure of accident circumstances and the selected keywords. Therefore, analysis of traffic accident data, specifically focusing on car-to-car accidents that occurred at street and signalized intersection on boulevard and avenue, was conducted. So the types of traffic accident situations and the corresponding accident counts were derived. Based on these situation types, 22 functional scenarios were developed to evaluate the driving safety of autonomous vehicle. In addition, a scenario pool was constructed for clustering and categorizing the multiple functional scenarios developed._x000D_ Through this study, a methodology of deriving types of traffic accident in the urban boulevard and avenue through spatial calculation and text mining from unstructured traffic accident data, and the process and results of developing functional scenarios based on this were presented. These developed functional scenario define various dangerous situations necessary to evaluate the driving safety of autonomous vehicle in urban boulevard and avenue roads, and used actual traffic accident data as the basis for scenario development to reflect the realistic traffic situations.
학위논문(석사)--D.N.A.플러스융합학과,2024. 2
Keywords: 시나리오; 자율주행자동차; 주행안전성